DAMPAK SOSIAL PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) PT. RIAU BARAHARUM DI DESA KELESA KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU - Yuni Sri Astuti; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted in the Village District of Seberida indolent Indragiri Hulu aimed to find out how to form the Social impact of the CSR program PT. Riau Baraharum against villagers indolent. This study entitled